A "Two‐in‐One" Strategy for Flexible Aqueous Batteries Operated at −80 °C. (5th April 2022) - Hu, Yin; Shi, Rongwei; Ren, Yongyuan; Peng, Wansu; Feng, Chengdong; Zhao, Yan; Zheng, Sijie; Li, Weizheng; Sun, Zhe; Guo, Jiangna; Guo, Siyu; Wang, Xiaoliang; et al.
Abstract: The development of aqueous metal‐ion batteries has attracted great attention due to their relatively low cost and high safety levels. However, their practical applications are hindered by the ease at which their aqueous electrolytes freeze. Inspired by the antifreezing properties of salts and alcohol cryoprotective agents, a "two‐in‐one" cryoprotective agent, hydroxyl‐functionalized poly(ionic liquid) (PIL‐OH)‐based hydrogel electrolyte for aqueous lithium‐ion batteries (ALIBs) is developed. The synergy of both ionic hydration and hydrogen bond interactions between the PIL‐OH and water molecules impairs the hydrogen‐bond networks of water and depresses the freezing point of water below −80 °C. Benefiting from exceptional ultralow temperature tolerance, the prepared PIL‐OH hydrogel exhibits a highly enhanced low temperature adaptability and a high ionic conductivity of 0.08 mS cm −1 at −80 °C. The PIL‐OH hydrogel‐based flexible ALIBs exhibit high flexible durability and good cycling stability with 93% capacity retention over 200 cycles at −80 °C. The PIL‐OH hydrogel report herein opens up new opportunities for practical applications of wearable and flexible aqueous batteries at ultralow temperature environments, such as the North and South Poles. Abstract : Inspired by the antifreezing properties of alcohol cryoprotective agents, a "two‐in‐one" cryoprotective agent, hydroxyl‐functionalized poly(ionic liquid) (PIL‐OH)‐based hydrogel electrolyte, with a low temperature adaptability and high ionic conductivity at −80 °C (0.08 mS cm −1 ) is prepared. The PIL‐OH hydrogel‐based flexible aqueous lithium‐ion batteries can be operated at an ultralow temperature of −80 °C.